If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + 2) * 2 = 0 Reorder the terms: (2 + m) * 2 = 0 Reorder the terms for easier multiplication: 2(2 + m) = 0 (2 * 2 + m * 2) = 0 (4 + 2m) = 0 Solving 4 + 2m = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2m = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 2m = 0 + -4 2m = 0 + -4 Combine like terms: 0 + -4 = -4 2m = -4 Divide each side by '2'. m = -2 Simplifying m = -2
| .5x+46=9x-5 | | 3-(x+8)=4-2(x+2) | | 2x-4x+5x-9x= | | 5h-7=2(h+14)-4h | | -1.1=-0.1p | | 7.3+t=36 | | 5x+x-16=14 | | 3u-10=44 | | 7.3+3=36 | | 3a+4a*4-2a+7a*7= | | -9a-81=-9(a+9) | | 2x-10=4(x+2) | | (4x-3)(16x-24x+9)=0 | | 235x=x+5 | | 3a+16a-2a+49a= | | y^2-4y-x+2=0 | | 7x^2-7x+84=0 | | -12/1/5= | | 3ln(2x+1)=18 | | 8(20+a)=6 | | e^3x=76 | | 3*7-5*-8= | | 211=170-y | | 3p-5q= | | 2+5*3-16= | | f(x)=3(sin^3)3x^3 | | (-6+4i)(2+1)= | | 15(3+s)=75 | | 8-(-2+8i)-(-7-i)= | | h=-.5*12 | | log(x+2)-log(x-7)=log(4) | | X^2-16X= |